PRIVATE MILITARY CONTRACTORS, WAR CRIMES AND INTERNATIONAL HUMANITARIAN LAW - Osakwe, Chukwuma; Umoh, Ubong Essien (Scientia Militaria - South African Journal of Military Studies, 2014)
The end of the Cold War witnessed the growth and spread of legally established private military contractors (PMCs) playing largely undefined roles in wars, international security and post-conflict reconstruction. The operations of PMCs in Iraq and Afghanistan in the 21st century have been marked by gross human rights abuses and poor treatment and torture of prisoners of war (POWs). Indeed, PMCs are likely to step outside their contractual obligations and commit criminal acts. This article adds to the literature on the subject by arguing that the elusiveness of PMCs’ individual or corporate responsibility for war crimes presents one of the greatest challenges for international humanitarian law (IHL). This presents a dilemma for IHL, which seeks to address individual offences. The situation becomes even more complicated when non-governmental organisations (NGOs) and multinational corporations (MNCs) are involved in the use of PMCs.